2021
DOI: 10.9734/ejnfs/2021/v13i230370
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Solvent Extraction on Phytochemicals and Antioxidant Activities from Fresh and Dried Wheatgrass

Abstract: Aims: This study was intended to investigate and quantify the phytochemicals and the antioxidant activities of fresh and powdered wheatgrass. Study Design:  The experiment was performed by solvent extraction technique for determining the phytochemicals of wheatgrass samples. Place and Duration of Study: The study was conducted at the Food engineering laboratory in Hajee Mohammad Danesh Science and Technology University, Dinajpur, Bangladesh between June 2018 and December 2018. Methodology: Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…From the TPC assay, it was concluded that the polyphenolic concentration in the ethanol and aqueous extracts is highest in those from grass harvested on the ninth day, and amounts to 61.5 and 107.1 mg GAE g −1 fresh sample respectively. Obtained results for TPC were about 50% higher than those reported in the literature for wheat grass 32 …”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…From the TPC assay, it was concluded that the polyphenolic concentration in the ethanol and aqueous extracts is highest in those from grass harvested on the ninth day, and amounts to 61.5 and 107.1 mg GAE g −1 fresh sample respectively. Obtained results for TPC were about 50% higher than those reported in the literature for wheat grass 32 …”
Section: Resultscontrasting
confidence: 69%
“…The flavonoid content followed the content of total polyphenols in EtOH extracts and was higher about four times than in wheat grass 32 …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The difference in the growth inhibitory effect between the crude extracts is probably due to the different content of compounds in the different medicinal plant species (Ganga Rao et al, 2012;Missau et al, 2014;Alsultan et al, 2016;Lalitha et al, 2017;Khoo et al, 2018;Pathak et al 2020;Syed et al, 2020;Ove et al, 2021;Wuryatmo et al, 2021). Flavonoids, alkaloids and tannins are frequently reported from the extracts of the nine medicinal plant species (Ganga Rao et al, 2012;Salome et al, 2012;Alsultan et al, 2017;Bhagyasri et al, 2017;Johri and Khan, 2017;Ayirezang et al, 2020;Syed et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, methanolic extraction was used in this study on the selected dietary supplements, which showed to be more significantly efficient and more phenolic compounds and other types of antioxidant properties than hexane and acetate extraction (36). In addition, past investigations showed that aqueous extraction could dissolve more polar compounds, for example, phenolic compounds with low and medium molecular weights and medium polarity (37).…”
Section: Antioxidant Activity Profilementioning
confidence: 99%